Developments in cybercrime law and practice in Ethiopia - Yilma, Kinfe Micheal (The computer law and security report, 2014)
With increasing access to information and communication technologies such as the Internet, Ethiopia has recently taken responsive legislative measures. One such legislative measure is enactment of cybercrime rules as part of the Criminal Code of 2004. These rules penalize three items of computer crimes namely hacking, dissemination of malware and denial of service attacks. The cybercrime rules are however slightly outdated due to changes that have occurred in the field of cybercrime since the enactment of the Code. The surge of new varieties of cybercrimes previously uncovered under the Code and the need to legislate tailored evidentiary and procedural rules for investigation and prosecution of cybercrimes have recently prompted the Ethiopian government to draft modern and comprehensive cybercrime legislation, but the draft law still needs further work on cybercrimes in light of other major legislative developments at regional and national levels. This article closely examines major developments in cybercrime law and practice in Ethiopia since the enactment of the first set of cybercrime rules and proffers recommendations towards a unified cybercrime regime.